2002
DOI: 10.1128/cdli.9.4.852-857.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychological Stress and Alprazolam on Development of Oral Candidiasis in Rats

Abstract: Psychological stress has been found to suppress cell-mediated immune responses that are important in limiting the proliferation of Candida albicans. Since anxiolytic drugs can restore cellular immunity in rodents exposed to stress conditions, we designed experiments conducted to evaluate the effects of alprazolam (1 mg/kg of body weight/day), a central benzodiazepine anxiolytic agonist, on the development of oral candidiasis in Sprague-Dawley rats exposed to a chronic auditory stressor. Animals were submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“… also found that injection of lipopolysaccharide provoked a significant increase in the circulating levels of corticosterone and alterations in cytokine levels, consistent with dysregulation of the immune system, in an animal model of depression. Psychological stress has been also shown to exacerbate oral infection with the opportunistic pathogen, Candida albicans , in rodents .…”
Section: Influence Of Psychosocial Factors In Periodontitismentioning
confidence: 99%
“… also found that injection of lipopolysaccharide provoked a significant increase in the circulating levels of corticosterone and alterations in cytokine levels, consistent with dysregulation of the immune system, in an animal model of depression. Psychological stress has been also shown to exacerbate oral infection with the opportunistic pathogen, Candida albicans , in rodents .…”
Section: Influence Of Psychosocial Factors In Periodontitismentioning
confidence: 99%
“…Nevertheless, taste and long-term use are common complaints from many patients. 9 Nystatin is a polyene macrolide whose toxicity is low if used as a topical medication, effective against most Candida species, and most often used to suppress local Candida infections. Antifungal polyene binds to elgosterol in the fungi cell membrane, so that there is a disruption in the structure of the cell membrane that causes intracellular leakage which ends in cell death.…”
Section: Discussionmentioning
confidence: 99%
“… 93 Moreover, psychological stress has been found to suppress cell-mediated immune responses that are important in inhibiting the growth of Candida albicans . 98 Stress and depression can also encourage unhealthy food choices, which indirectly facilitate the shift in bacterial species based on the micronutrient profile of the food consumed. 97 A high-saturated-fat diet, for example, can alter the vaginal microbiota by decreasing lactobacilli species dominance, which raises the risk of bacterial vaginosis.…”
Section: The Dynamic Protection Of the Vulva And Vaginamentioning
confidence: 99%